2011
DOI: 10.1093/hmg/ddr509
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing identifies mutations in Atonal homolog 7 (ATOH7) in families with global eye developmental defects

Abstract: The atonal homolog 7 (ATOH7) gene encodes a transcription factor involved in determining the fate of retinal progenitor cells and is particularly required for optic nerve and ganglion cell development. Using a combination of autozygosity mapping and next generation sequencing, we have identified homozygous mutations in this gene, p.E49V and p.P18RfsX69, in two consanguineous families diagnosed with multiple ocular developmental defects, including severe vitreoretinal dysplasia, optic nerve hypoplasia, persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 52 publications
1
54
0
1
Order By: Relevance
“…RGC survival is believed to reflect the formation of functional synaptic connections in the brain [10]. disease in humans [15][16][17], with optic nerve aplasia being the primary phenotype in both species. Recent genome-wide association studies (GWAS) have identified the ATOH7 locus as a major determinant of variation in the optic disc area in normal human populations [3][4][5] and a contributing factor in the susceptibility to glaucoma disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…RGC survival is believed to reflect the formation of functional synaptic connections in the brain [10]. disease in humans [15][16][17], with optic nerve aplasia being the primary phenotype in both species. Recent genome-wide association studies (GWAS) have identified the ATOH7 locus as a major determinant of variation in the optic disc area in normal human populations [3][4][5] and a contributing factor in the susceptibility to glaucoma disease [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…2,4 The disease can be regarded as a spectrum disorder of familial exudative vitreoretinopathy (FEVR) that is a highly heterogeneous clinical and genetic disorder manifested by an incomplete retinal vascular development. 3,5,7,8 FEVR is genetically heterogeneous, and nearly one-half of FEVR patients have mutations in five genes, viz., the FZD4, LRP5, NDP, TSPAN12, and ZNF408 genes. 9,10 The protein of the ATOH7 gene is a transcription factor that plays a crucial role in ocular embryogenesis and is required for the development of the retinal ganglion cells.…”
mentioning
confidence: 99%
“…Recently, mutations in the ATOH7 gene were identified in families with nonsyndromic CRNA and related conditions. 3,7,8 We have identified a homozygous mutation in the ATOH7 gene in a patient with CRNA. Initially, we performed mutational analyses of the ATOH7 gene on 64 unrelated Japanese patients with FEVR of various phenotypes including CRNA who had no mutations in the known FEVR-causing genes, FZD4, LRP5, NDP, TSPAN12, and ZNF408 (Supplemental Table 1 online only).…”
mentioning
confidence: 99%
“…ATOH7 se encuentra ubicado en 10q21.3 47 y recientemente se han identificado mutaciones en pacientes con microftalmia y otras anomalías del desarrollo ocular, como persistencia del vítreo primario hiperplásico 48,49 .…”
Section: Atoh7unclassified